1989
DOI: 10.1139/g89-519
|View full text |Cite
|
Sign up to set email alerts
|

C-banding and DNA content in seven species of Tenebrionidae (Coleoptera)

Abstract: The relative amount of C-banded heterochromatin varies strikingly in seven species of tenebrionid beetles, from 25 to 58%, but most species show procentric bands only. Nevertheless, Gonocephalum patruele exhibits an almost completely heterochromatic X chromosome. The nuclear DNA content of Feulgen-stained spermatids has yielded up to a threefold difference, from 0.27 to 0.86 pg, which is not completely in accordance with the amount of C-banded heterochromatin. However, the genome sizes correlate significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 16 publications
6
59
1
Order By: Relevance
“…This pattern of distribution has been described for most coleopteran species studied by C-banding (Virkki, 1983;Rozek and MaryanskaNadachowska, 1991;Rozek and Rudek, 1992), although telomeric blocks in addition to pericentromeric ones have been observed in the tenebrionid Misolampus goudoti (Juan and Petitpierre, 1989) and exclusively telomeric blocks in the carabid Bembidion minimum (Rozek and Rudek, 1992), with extra-heterochromatic segments having been reported in the scarabaeid Bubas bison (Colomba et al, 1996).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This pattern of distribution has been described for most coleopteran species studied by C-banding (Virkki, 1983;Rozek and MaryanskaNadachowska, 1991;Rozek and Rudek, 1992), although telomeric blocks in addition to pericentromeric ones have been observed in the tenebrionid Misolampus goudoti (Juan and Petitpierre, 1989) and exclusively telomeric blocks in the carabid Bembidion minimum (Rozek and Rudek, 1992), with extra-heterochromatic segments having been reported in the scarabaeid Bubas bison (Colomba et al, 1996).…”
Section: Discussionsupporting
confidence: 59%
“…Differential techniques have rarely been applied to chromosome studies of the Coleoptera, but data from the species so far analyzed have shown that the autosomal constitutive heterochromatin (CH) is preferentially located on pericentromeric region and is less frequent on interstitial and telomeric regions while the position of sex chomosome constitutive heterochromatin is more variable in that it may be pericentromeric or entirely heterochromatic (Vidal et al, 1977;Angus, 1983;Drets et al, 1983;Virkki, 1983;Juan and Petitpierre, 1989;Rozek and Lachowska, 2001). Base-specific fluorochromes have provided important information regarding the composition of CH in coleopteran species of the families Tenebrionidae (Juan and Petitpierre, 1989;Plohl et al, 1993) and Scarabaeidae (Colomba et al, 1996;Colomba et al, 2000;Moura et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Coleoptera constitute the largest animal group with more than 350,000 described species (Lawrence, 1982). The family Tenebrionidae is very conservative in terms of karyological evolution; nearly 60 per cent of the 200 species studied have 2n =20 chromosomes (Juan & Petitpierre, 1990) but some species are known to contain large blocks of heteropycnotic chromatin in meiocytes (Smith, 1952) and variable amounts of C-banding positive chromosomal material (Juan & Petitpierre, 1989). Tenebrio molitor is the only beetle where the satellite DNA has been characterized (Petitpierre et al 1988;Davis & Wyatt, 1989;Ugarkovic et at., 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In coleopterans there are relatively few reports of chromosome banding (Ennis, 1974;Angus, 1983;Virkki and Denton, 1987;Juan and Petitpierre, 1989), probably because of the small size of their chromosomes and the poor resolution of longitudinal differentiation obtained with conventional techniques. In most cases, the individual identification of all chromosomes is difficult due to the similarities of size and shape.…”
Section: Introductionmentioning
confidence: 99%